2020
DOI: 10.1186/s12886-020-01334-y
|View full text |Cite
|
Sign up to set email alerts
|

Diacron reactive oxygen metabolites and biological antioxidant potential tests for patients with age-related macular degeneration

Abstract: Background: Previously, we showed that serum malondialdehyde (MDA) was significantly higher in patients with neovascular age-related macular degeneration (nAMD) than in those without AMD. The Diacron reactive oxygen metabolites (d-ROMs) and biological antioxidant potential (BAP) tests are known markers of oxidative stress. The aim of this study was to use d-ROMs and BAP tests to evaluate changes in systemic oxidative stress in patients with nAMD. Methods: Blood serum samples were collected from 34 patients wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…The analysis of comparison between the genders revealed the d-ROMs was significantly higher in women. This result agrees with other studies carried out in healthy individuals (47) and individuals with various pathologies (35,43,46,49,59,66). One of the possible explanations for this result is the hormonal changes in women associated with blood concentrations of estrogen and, therefore, on menopausal status (46).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The analysis of comparison between the genders revealed the d-ROMs was significantly higher in women. This result agrees with other studies carried out in healthy individuals (47) and individuals with various pathologies (35,43,46,49,59,66). One of the possible explanations for this result is the hormonal changes in women associated with blood concentrations of estrogen and, therefore, on menopausal status (46).…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies have demonstrated the usefulness and effectiveness of the evaluation of the redox state through these two tests, both in the evaluation in humans and in animals(11,14,36,42,43,47,(58)(59)(60) however, this is the first time that there was a correlation investigation of both parameters with a wide range of hematological and biochemical variables.The evaluation of the redox state in the present study identified that the d-ROMs values were above normal levels (420.2 ± 112.1 U CARR), while the BAP test value was within the levels considered adequate (2332 ± 812 µmol/l). In addition, blood markers of inflammation, CRP, RDW, and Plt correlated positively with d-ROMs, OSI and negatively with BAP/dROMs (except the RDW).…”
mentioning
confidence: 99%
“…The biological antioxidant potential (BAP) level was measured as a marker of oxidative stress. Measurement of the BAP concentrations (Diacron International, Grosseto, Italy) was performed using a spectrophotometer, as reported previously [ 51 ].…”
Section: Methodsmentioning
confidence: 99%